Stock Market Performance, Carbon Emissions and Economic Growth in Nigeria and Ghana - Irejeh, Enaikpobomene Mina & Aninoritse, Lisa Edafiaje (Quest Journals Journal of Research in Business and Management, 2024)
This study seeks to investigate the application of FF3FM in the Nigerian stock market. The study examined the behaviour of stock returns in relation to market beta, firm size (market equity), and book-to-market equity (BE/ME) factors. Sixtyeight (68) sample size was selected from all stocks quoted on the Nigerian Stock Exchange (NSE) from 2013 to 2022. Time series regression analysis was adopted. Monthly excess portfolio returns were regressed on firm size, excess market returns and book-to-market-equity ratio. The findings showed a strong correlation between book-to-market equity variables, firm size, and excess stock market returns and predicted portfolio returns. This suggests that the variation in stock returns in the Nigerian stock market can be explained by the FF3FM.
Keywords: Asset pricing; Stock return; CAPM; excess market returns and book to market equity ratio